On the multivariate analysis of the Lisbon process - Arno Tausch; Almas Heshmati; Chemen S.J. Bajalan (Institute for the Study of Labor (IZA), 2007)
Starting from Professor Kornai's assertion about the necessity to focus on the long-term perspectives of the transformation process, we analyze in this paper the Lisbon performance of the countries of the European Union from such a long-term, structural perspective. We present in a simple form the mathematical methods used in this essay. Then, we analyze Lisbon indicator performance by factor analytical means. We conclude that only a Schumpeterian vision of capitalism as a process of creative destruction - or rather - destructive creation can explain these contradictions, which we empirically reveal in this analysis, and which beset the Lisbon process from the very beginning. Our factor analysis tells us that a majority of the kernel Lisbon indicators go indeed hand in hand with high comparative price levels; high freight transport; high greenhouse gas emissions; low business investment rates; and low youth educational attainment rates. We conclude that in reality we are facing four underlying and contradictory processes including a Lisbon productivity factor; high eco-social exclusion; the employment performance; and the neo-liberal European model.
Keywords: C43; 330; Index numbers and aggregation; cross-sectional models; spatial models; economic integration; regional economic activity; international factor movements; international business; international relations; international political economy; Wirtschaftliche Anpassung; Entwicklungskonvergenz; Lissabon Strategie; Wirtschaftswachstum; Internationaler Wettbewerb; EU-Staaten; EU-Staaten (Osteuropa)